Compliance relationship analysis between environmental governance attention and environmental quality in the Beijing–Tianjin–Hebei region - Lin Wang; Feng Pan; Xiaojing Li (Frontiers in Environmental Science, 2023)
This study analyzes the changes and allocation characteristics of environmental governance attention in the Beijing–Tianjin–Hebei region based on the government work report from 2002 to 2020 and explores the compliance relationship between environmental governance attention and environmental quality. The results show that the allocation of local government environmental governance attention shows high consistency with that of the central government, and the overall environmental governance attention shows a fluctuating upward trend. There is a long-term stable co-integrated relationship between environmental governance attention and environmental quality in the Beijing–Tianjin–Hebei region, as well as a two-way Granger causality relationship in the short term. The non-linear influence of environmental governance attention on the environmental quality in the Beijing–Hebei–Tianjin region can be described using the LSTR2 model. During 2004–2016, environmental governance attention often had non-linear effects on the environmental quality. Since 2016, there has been a stable linear relationship between environmental governance attention and environmental quality. Finally, some policy suggestions on improving the local performance evaluation system and establishing a collaborative environment system for the Beijing–Tianjin–Hebei region have been put forward for the government.